Human resource management /Robert L. Mathis, University of Nebraska at Omaha, John H. Jackson, University of Wyoming, Sean R. Valentine, University of North Dakota, Patricia A. Meglich, University of Nebraska at Omaha. - Jackson, Jonh H.
Includes bibliographical references and indexes.